2023
DOI: 10.3233/cbm-210559
|View full text |Cite
|
Sign up to set email alerts
|

MKRN1/2 serve as tumor suppressors in renal clear cell carcinoma by regulating the expression of p53

Abstract: BACKGROUND: Kidney renal clear cell carcinoma (KIRC) belongs to renal cell carcinoma which is a very aggressive malignant tumor with poor prognosis and high mortality. The MKRN family includes three members MKRN1, MKRN2 and MKRN3, which are closely related to cancers, and have been involved in many studies. OBJECTIVE: This study aimed to explore the roles of MKRN family in KIRC. METHODS: The expression of MKRNs was analyzed using the UALCAN database, prognostic analysis was performed with the GEPIA2 and Kaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Furthermore, flow cytometry analysis revealed that MKRN1 knockdown impeded the transition of HeLa cells from the G0/G1 phase to the S phase, indicating a role for MKRN1 in regulating the cell cycle. Our findings were consistent with previous studies that have identified MKRN1 as a key regulator of cell proliferation in various cancer types, such as pancreatic cancer 15 , renal clear cell carcinoma 16 , and colorectal cancer 17 . Further research is needed to elucidate the molecular mechanisms underlying the role of MKRN1 in regulating cancer cell migration and invasion.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, flow cytometry analysis revealed that MKRN1 knockdown impeded the transition of HeLa cells from the G0/G1 phase to the S phase, indicating a role for MKRN1 in regulating the cell cycle. Our findings were consistent with previous studies that have identified MKRN1 as a key regulator of cell proliferation in various cancer types, such as pancreatic cancer 15 , renal clear cell carcinoma 16 , and colorectal cancer 17 . Further research is needed to elucidate the molecular mechanisms underlying the role of MKRN1 in regulating cancer cell migration and invasion.…”
Section: Discussionsupporting
confidence: 93%